Effect of subcritical water pre-treatment on delignification of empty fruit bunches (EFB) - Norshuhadah Ahmad
The oil palm industry is one of the biggest industries in Malaysia and it generates the most biomass. Production of abundant palm oil mill waste was not utilised properly. Burning is the traditional method of disposal of this waste that generates greenhouse gases and pollutes the air. Empty fruit bunch (EFB) are a few examples of the plentiful biomass waste generated from the palm oil industry. The main objective of this study is to investigate the factors affecting the delignification of empty fruit bunch (EFB) by subcritical water pretreatment. Subcritical water pretreatment with solid to water ratio (1:6-1:10), temperature (120°C -180°C), and reaction time (10 min - 30 min) was chosen to disrupt the recalcitrance structure of the complex lignocellulosic structure of EFB. Then, chemical characterization of extractives, lignin, hemicellulose, holocellulose, and a-cellulose was done on both untreated and treated EFB. Response Surface Methodology (RSM) was used to obtain the optimum parameters for the subcritical water pretreatment of EFB using a Central Composite Design in the Design Expert Software. The optimization was conducted to examine the effects of three independent variables, which are temperature (°C), reaction time (minutes), and solvent to solid ratio (mL/g), on the outcome which are cellulose (%), hemicellulose (%) and lignin (%). Subcritical water retains the majority of the cellulose while removing almost all the hemicellulose. Hemicelluloses solubilise at high temperatures and has amorphous structure hence reducing the content of hemicellulose is reduced. Overall, the sub-critical water pre-treatment helped in solubilizing complex organic materials. The temperature of 120 °C, reaction duration of 10 min, and a solid to water ratio of 1:6 were the ideal parameters for EFB delignification with chemical characterization of 46.881% cellulose, 27.125% hemicellulose, and 24.278% lignin.